Intervalo hídrico ótimo em solo sob rotação de culturas e escarificação - Calonego, Juliano Carlos; Rosolem, Ciro Antonio [UNESP] (FapUNIFESP (SciELO), 2011)
Soil water availability to plants is affected by soil compaction and other variables. The Least Limiting Water Range (LLWR) comprises soil physical variables affecting root growth and soil water availability, and can be managed by either mechanical or biological methods. There is evidence that effects of crop rotations could last longer than chiseling, so the objective of this study was to assess the effect of soil chiseling or growing cover crops under no-till (NT) on the LLWR. Crop rotations involving triticale (X Triticosecale) and sunflower (Helianthus annuus) in the fall-winter associated with millet (Pennisetum glaucum), sorghum (Sorghum bicolor) and sunn hemp (Crotalaria juncea) as cover crops preceding soybean (Glycine max) were repeated for three consecutive years. In the treatment with chiseling (performed only in the first year), the area was left fallow between the fall-winter and summer crops. The experiment was carried out in Botucatu, São Paulo State, Brazil, from 2003 to 2006 on a Typic Rhodudalf. The LLWR was determined in soil samples taken from the layers 0-20 cm and 20-40 cm, after chemical desiccation of the cover crops in December of the first and third year of the experiment. Chiseling decreases soil bulk density in the 0-20 cm soil layer, increasing the LLWR magnitude by lowering the soil water content at which penetration resistance reaches 2.0 MPa; this effect is present up to the third year after chiseling and can reach to a depth of 0.40 m. Crop rotations involving sunflower + sunn hemp, triticale + millet and triticale + sunn hemp for three years prevented soil bulk density from exceeding the critical soil bulk density in the 0-0.20 m layer. This effect was observed to a depth of 0.40 m after three years of chiseling under crop rotations involving forage sorghum. Hence, chiseling and some crop rotations under no tillage are effective in increasing soil quality assessed by the LLWR.
Least limiting water range in soil under crop rotations and chiseling
Keywords: Cover crops; Crop rotation; No till; Soil compaction; Soil water